Sólitons de Ricci gradiente shrinking - Gondim, Antônio Mateus Barreto (2020)
The main purpose of this work is to study the geometry of noncompact gradient shrinking Ricci solitons. Ricci solitons are self-similar solutions of the Ricci flow, which appear as singularities of the Ricci flow. We present a proof to the growth estimate of the potential function of a complete noncompact gradient shrinking Ricci soliton. In addition, we present that such solitons have at most polynomial volume growth. Both results were proved originally by Huai-Dong Cao and Detang Zhou in 2010.